Real-time cationic sensing using plasmonic fiber optic sensor based phosphoryl-carrageenan - Bakar M.H.A.; Azeman N.H.; Mobarak N.N.; Nazri N.A.A.; Mohd Daniyal W.M.E.M.; Zan M.S.D.; Mahdi M.A.; Zain A.R.M.; Gupta R.; Abdullah F.; Bakar A.A.A. (Elsevier B.V., 2025)
We report Fiber Optic-Localized Surface Plasmon Resonance (FO-LSPR) spectroscopy sensors comprising a coating of spherical silver nanoparticles (AgNPs) embedded in phosphoryl-carrageenan. This is a novel report on modified carrageenan namely phosphoryl-carrageenan as sensing materials for cations specifically ammonium ions (NH4+). The morphology of carrageenan and phosphoryl-carrageenan coatings on the fiber optic probe was uneven and wavelike topography, indicating the successful coating on the fiber optic probe surface. The FO-LSPR showed a distinct dip in reflectivity in the region of 370?400 nm due to the resonance frequency of spherical AgNPs. The response and recovery times of FO-LSPR sensors for 1 ppm NH4+ and deionized water were <20 s and ?1.2 minutes, respectively, with five times stable repeatability. The sensitivity of the FO-LSPR phosphoryl-carrageenan was 3.441 nm/ppm. Equally, the limits of detection and quantitation of fiber optic FO-LSPR were 0.336 and 1.018 ppm, respectively. Meanwhile, the dynamic range of the FO-LSPR was 0.3 ? 2.0 ppm. The proposed sensor demonstrated strong selectivity towards NH4+ over common cationic interferents. Furthermore, the reported FO-LPSR sensor offered a comparable measurement performance to current methods, while being low cost and portable, and allowing in-situ real-time monitoring of cation ammonium. Thus, reported FO-LPSR sensors are highly promising for water monitoring applications. ? 2024 Elsevier B.V.